Viral oncogene EBNALP regulates YY1 DNA binding and alters host 3D genome organization - Wang, Chong; Leong, Merrin Manlong; Ding, Weiyue; Narita, Yohei; Liu, Xiang; Wang, Hongbo; Yiu, Stefanie P T; Lee, Jessica; Zhao, Katelyn R S; Cui, Amy; Gewurz, Benjamin; Hammerschmidt, Wolfgang; et al. (EMBO reports, 2025)
The Epstein–Barr virus (EBV) nuclear antigen leader protein (EBNALP) is essential for the immortalization of naive B lymphocytes (NBLs). However, the mechanisms remain elusive. To understand EBNALP’s role in B-cell transformation, we compare NBLs infected with wild-type EBV and an EBNALP-null mutant EBV using multi-omics techniques. EBNALP inactivation alters enhancer–promoter interactions, resulting in decreased CCND2 and increased CASP1 and BCL2L11 expression. Mechanistically, EBNALP interacts with and colocalizes with the looping factor YY1. Depletion of EBNALP reduces YY1 DNA-binding and enhancer–promoter interactions, similar to effects observed with YY1 depletion. Furthermore, EBNALP colocalizes with DPF2, a protein that binds to H3K14ac and H4K16ac. CRISPR depletion of DPF2 reduces both EBNALP and YY1 DNA binding, suggesting that the DPF2/EBNALP complex may tether YY1 to DNA to increase enhancer–promoter interactions. EBNALP inactivation also increases enhancer–promoter interactions at the CASP1 and BCL2L11 loci, along with elevated DPF2 and YY1 binding and DNA accessibility. Our data suggest that EBNALP regulates YY1 to rewire the host genome, which might facilitate naive B-cell transformation. Synopsis EBNALP alters looping factor YY1 DNA binding and 3D genome organization which might facilitate cell cycle progression and prevent cell death. EBNALP is tethered to DNA by DPF2. EBNALP recruits YY1 to the CCND2 locus and increases enhancer-promoter interaction and gene expression. EBNALP reduces DNA accessibility and limits YY1 DNA binding at the BCL2L11 locus, reducing enhancer-promoter looping and gene expression. EBNALP alters looping factor YY1 DNA binding and 3D genome organization which might facilitate cell cycle progression and prevent cell death.